Beyond 2020: Malay and Indonesian in a New Linguistic World Order (KEMANUSIAAN The Asian Journal of Humanities, 2011)
This article departs from a discussion of Graddol's (1997) prediction that the hierarchy of world languages will change between 1997 and 2050. Current monopoly languages like English and French, notably, are forecast to be replaced by an oligopoly of languages led by Chinese, Hindi/Urdu, English, Spanish and Arabic by the year 2050. In order to examine this general assertion, a bibliometric case study of the foreign-language books on Malaysia and Indonesia is conducted. It is shown that no trend of the emergence of a new oligopoly of world languages or a beginning of such a trend can be observed. Neither Chinese nor Hindi/Urdu, Spanish or Arabic have gained any significant role that would be comparable to that of English. Further, by comparing the current flows of international student migration with the rankings of the world's top 400 universities, it is argued that the share of the English-language cluster might be even increasing slightly in the foreseeable future. Finally, the economic relevance of the world's most important languages is assessed, through a weighted calculation of the Gross Domestic Product (GDP) of the world's countries and territories in relation to the languages used in these countries. In general, the English-language cluster seems to remain unchallenged as the world's most important academic and economic language. From Graddol's five new leading languages, only Chinese seems to be making some considerable advances in the economic field, while it is not yet a major international academic language. Instead, languages such as Japanese, German, French and Spanish seem to continue to play relevant roles, albeit only secondary to English.